2011
DOI: 10.1007/s00795-010-0532-1
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma promotes epithelialization and angiogenesis in a splitthickness skin graft donor site

Abstract: Autologous platelet-rich plasma contains multiple growth factors. We performed a side-by-side (half-side) test between the platelet-rich plasma (PRP)-treated and control (untreated) sides of a split-thickness skin graft donor site, and compared the number of days until epithelialization and pain during gauze change. On day 13 after surgery, we performed punch biopsy on the two sides and for adjacent normal skin tissue and compared the epidermal thickness and numbers of collagen fibers and newly formed vessels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 17 publications
5
43
0
Order By: Relevance
“…This series witnessed improvement in the wound healing in the PRP side as evident by the significant increase in the epithelialization surface area in the PRP side at days 7 and 14 postoperative (p < 0.001 and p = 0.039 respectively). Similar to our study and findings, Kakudo et al [16] studied the effect of PRP on the donor site of STSG and noticed macroscopic epithelialization on the 5 th day of PRP application. In another study, Spyridakis et al [17] noted that complete wound closure was statistically faster in the PRP treated wounds.…”
Section: Discussionsupporting
confidence: 92%
“…This series witnessed improvement in the wound healing in the PRP side as evident by the significant increase in the epithelialization surface area in the PRP side at days 7 and 14 postoperative (p < 0.001 and p = 0.039 respectively). Similar to our study and findings, Kakudo et al [16] studied the effect of PRP on the donor site of STSG and noticed macroscopic epithelialization on the 5 th day of PRP application. In another study, Spyridakis et al [17] noted that complete wound closure was statistically faster in the PRP treated wounds.…”
Section: Discussionsupporting
confidence: 92%
“…These characteristics of platelets have led to the idea of using platelets as therapeutic tools to promote wound healing, particularly in patients whose tissue repair is significantly impaired or delayed [1]. We previously reported that PRP promoted fibroblast growth [2] and induced epithelialization and neovascularization at split thickness skin graft donor sites [6]. Other investigators have used platelet growth factors to treat nonhealing wounds [7].…”
Section: Discussionmentioning
confidence: 99%
“…Klosová et al reported that combination of split-thickness skin grafting (STSG) and autologous platelet concentrate reversed the viscoelastic properties of scars to the plateau state more rapidly than areas treated with STSG alone [77][78][79].…”
Section: Prp In Burnsmentioning
confidence: 99%